Respuesta :
Answer:
a. substitute 2 into each expression, and evaluate them
Step-by-step explanation:
The given expressions are not equivalent and Ahmed determined this by substituting 2 into each expression and evaluating them.
Given :
Ahmed wrote the two expressions -- (3/4 (8x + 4 )); (6x +1)
The following steps can be used in order to determine the procedure that Ahmed follow to determine if the two expressions are equivalent:
Step 1 - Write the given expression.
3/4 (8x + 4) --- (1)
6x + 1 --- (2)
Step 2 - Now, substitute the value of (x = 2) in the expression (1).
[tex]= \dfrac{3}{4}\times ((8\times2) + 4)[/tex]
[tex]=3\times 5[/tex]
= 15
Step 3 - Now, substitute the value of (x = 2) in the expression (2).
= 6(2) + 1
= 13
From the above steps, it can be concluded that the given expressions are not equivalent. Therefore, the correct option is a).
For more information, refer to the link given below:
https://brainly.com/question/11897796